INTERPERSONAL TRUST WITHIN AN ORGANIZATION BASED ON HIERARCHICAL CONTEXT: TOWARDS IMPROVING ORGANIZATIONAL EFFICIENCY IN CHINA - Law, K ian Aun; Bhaumik, Amiya; Sun, Peng; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
This study tested the self-designed trust development-oriented subordinate behavioral characteristics and explored the structural dimensions of subordinate behavioral characteristics affecting the trust development of subordinates through statistical analysis. Trust-based and involvement-oriented management is an important source of the competitive advantage of an organization. The largest host of research results implies that interpersonal trust in an organization is of great significance to the organization and can improve the effectiveness of the organization and its members as well. On this basis, adaptation of questionnaire items was revised and formal questionnaires were formed. The findings of this paper provided that, with the understanding of core theme of the trust between superior and subordinate in an organization, it starts with the trust-oriented superior and subordinate behavior characteristics, and comprehensively expedients the inter-level model of trust development between superior and subordinate in an organization. It is achieved by combining the factors of organizational control system, which leading towards organizational efficiency.